2010
DOI: 10.1021/np100423w
|View full text |Cite
|
Sign up to set email alerts
|

Xylorumphiins A−D, Mexicanolide Limonoids from the Seed Kernels of Xylocarpus rumphii

Abstract: Four new mexicanolide limonoids, named xylorumphiins A-D (1-4), were isolated from the seed kernels of Xylocarpus rumphii, together with three known limonoids. Their structures and configurations were established on the basis of spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
(43 reference statements)
2
17
0
Order By: Relevance
“…From the perspective of the NPs researcher, NMR has recently experienced major gains in sensitivity due to the development of micro-cryoprobe technology. Martin and co-workers 35,36 (and references therein) are among the leaders in this field and have demonstrated the feasibility of acquiring a 2D gHSQC spectrum of 540 ng of strychnine ( 6 ) at 600 MHz utilizing a weekend of spectrometer time. Along the lines of low-level/high-sensitivity qHNMR, Weljie et al described a method for the detection and quantitation of low-intensity unknown peaks (LIUPs) in spiked urine samples.…”
Section: The Qhnmr Experimentsmentioning
confidence: 99%
“…From the perspective of the NPs researcher, NMR has recently experienced major gains in sensitivity due to the development of micro-cryoprobe technology. Martin and co-workers 35,36 (and references therein) are among the leaders in this field and have demonstrated the feasibility of acquiring a 2D gHSQC spectrum of 540 ng of strychnine ( 6 ) at 600 MHz utilizing a weekend of spectrometer time. Along the lines of low-level/high-sensitivity qHNMR, Weljie et al described a method for the detection and quantitation of low-intensity unknown peaks (LIUPs) in spiked urine samples.…”
Section: The Qhnmr Experimentsmentioning
confidence: 99%
“…Compounds 1, 3, 5, and 24-29 were isolated from seed kernels of X. granatum [23], whereas 8-10 were obtained from X. moluccensis [24], both of which were collected in Samutsongkram province. Compounds 7,[11][12][15][16], and 23 were isolated from X. moluccensis collected in Phuket [26], and compounds 17-22 were isolated from X. rumphii from Rayong province [25]. Compounds 2, 4, 6, and 31 were obtained from X. granatum, while 13-14 and 30 were isolated from X. moluccensis, both of which were from Suratthani province (Supporting Information).…”
Section: Origin and Purity Of Tested Limonoidsmentioning
confidence: 99%
“…Additionally, the bark pressings of both Xylocarpus granatum and Xylocarpus moluccensis are utilized to treat cholera and fever, including that caused by malaria. Recently we reported the isolation and identification of a number of limonoids from the seeds of three Thai mangroves in this genus, X. granatum, X. moluccensis, and X. rumphii [23][24][25][26]. As part of an ongoing program to search for anti-inflammatory agents from Thai natural products and based on the activity of the extracts of the Xylocarpus plants, the present study was undertaken to evaluate the effects of isolated limonoids on inflammatory responses and to investigate the molecular mechanism of action of selected limonoids.…”
mentioning
confidence: 99%
“…(Table 2) indicated that 7 units of these 13 unsaturations came from three carbon-carbon double bonds and four ester carbonyls, the other 6 units of unsaturations coming from six rings. In addition, a quaternary carbon at C 107.41 was assignable to C-1, a hemiacetal group related to that found in xylocessin F 14) and xylorumphiin C, 15) (Fig. 3).…”
Section: Resultsmentioning
confidence: 86%
“…12,14,15) Significant NOESY correlations from H-3 to Me-29 ( H 0.79, s), but not from H-3 to H-5, nor from H-3 to H-30 implied that H-3 was -oriented. The correlations of H-9 ( H 2.14, o)/Me-18 ( glioma (U251-SP), and breast (MCF-7) cancer cell lines (IC 50 >100 mM).…”
Section: Resultsmentioning
confidence: 99%